Robotic Surgery for Rectal Cancer Treatment: Clinical Outcomes and Quality of Life. Comparison of Surgical Methods - Raminta Akelaitytė; Justas Žilinskas (Lietuvos Chirurgija)
Background. Rectal cancer is one of the most common oncological diseases in the world. In recent years, robotic surgery has been increasingly used to improve the outcome of this disease. Aim. To review the latest scientific literature on the application of robotic surgery in the treatment of rectal cancer and to evaluate clinical outcomes in patients. Material and methods. The research method is a literature review. Publications were researched in the PubMed and Google Scholar databases using the following keywords and their combinations in English: rectal cancer, robotic surgery, laparoscopic surgery, open surgery. Based on the inclusion and exclusion criteria, 68 scientific publications were included in the review.